CCR5 Expression Levels in HIV-Uninfected Women Receiving Hormonal Contraception. (20th April 2015) - Sciaranghella, Gaia; Wang, Cuiwei; Hu, Haihong; Anastos, Kathryn; Merhi, Zaher; Nowicki, Marek; Stanczyk, Frank Z.; Greenblatt, Ruth M.; Cohen, Mardge; Golub, Elizabeth T.; Watts, D. Heather; Alter, Galit; et al.
Abstract : Human immunodeficiency virus (HIV) infectivity increases as receptor/coreceptor expression levels increase. We determined peripheral CD4, CCR5, and CXCR4 expression levels in HIV-uninfected women who used depot medroxyprogesterone acetate (DMPA; n = 32), the levonorgestrel-releasing intrauterine device (LNG-IUD; n = 27), oral contraceptive pills (n = 32), or no hormonal contraception (n = 33). The use of LNG-IUD increased the proportion of CD4 + and CD8 + T cells that expressed CCR5; increases in the magnitude of T-cell subset CCR5 expression were observed with DMPA and LNG-IUD use ( P < .01 for all comparisons). LNG-IUD and, to a lesser extent, DMPA use were associated with increased peripheral T-cell CCR5 expression.